Selective benzylic C–H monooxygenation mediated by iodine oxides - LaMartina, Kelsey B.; Kuck, Haley K.; Oglesbee, Linda S.; Al-Odaini, Asma; Boaz, Nicholas C. (Beilstein Journal of Organic Chemistry, 2019)
A method for the selective monooxdiation of secondary benzylic C–H bonds is described using an N-oxyl catalyst and a hypervalent iodine species as a terminal oxidant. Combinations of ammonium iodate and catalytic N-hydroxyphthalimide (NHPI) were shown to be effective in the selective oxidation of n-butylbenzene directly to 1-phenylbutyl acetate in high yield (86%). This method shows moderate substrate tolerance in the oxygenation of substrates containing secondary benzylic C–H bonds, yielding the corresponding benzylic acetates in good to moderate yield. Tertiary benzylic C–H bonds were shown to be unreactive under similar conditions, despite the weaker C–H bond. A preliminary mechanistic analysis suggests that this NHPI-iodate system is functioning by a radical-based mechanism where iodine generated in situ captures formed benzylic radicals. The benzylic iodide intermediate then solvolyzes to yield the product ester.
Keywords: acetoxylation; benzylic; iodate; NHPI; oxidation; radical

(untitled) - Bordwell, F. G.; Cheng, J. P.; Harrelson, J. A. (J. Am. Chem. Soc., 1988)

(untitled) - Xue, X.-S.; Ji, P.; Zhou, B.; Cheng, J.-P. (Chem. Rev., 2017)

(untitled) - Dash, S.; Patel, S.; Mishra, B. K. (Tetrahedron, 2009)

(untitled) - Rangarajan, R.; Eisenbraun, E. J. (J. Org. Chem., 1985)

Oxidation: Techniques and Applications in Organic Synthesis - Lee, D. G. (Hydrocarbon Oxidation, 1969)

(untitled) - Punniyamurthy, T.; Velusamy, S.; Iqbal, J. (Chem. Rev., 2005)

(untitled) - Gunay, A.; Theopold, K. H. (Chem. Rev., 2010)

(untitled) - Lee, N. H.; Lee, C.-S.; Jung, D.-S. (Tetrahedron Lett., 1998)

(untitled) - Nagano, T.; Kobayashi, S. (Chem. Lett., 2008)

(untitled) - Shen, D.; Miao, C.; Wang, S.; Xia, C.; Sun, W. (Org. Lett., 2014)

(untitled) - Sterckx, H.; De Houwer, J.; Mensch, C.; Herrebout, W.; Tehrani, K. A.; Maes, B. U. W. (Beilstein J. Org. Chem., 2016)

(untitled) - Yang, Y.; Ma, H. (Tetrahedron Lett., 2016)

(untitled) - Jurado-Gonzalez, M.; Sullivan, A. C.; Wilson, J. R. H. (Tetrahedron Lett., 2003)

(untitled) - Modica, E.; Bombieri, G.; Colombo, D.; Marchini, N.; Ronchetti, F.; Scala, A.; Toma, L. (Eur. J. Org. Chem., 2003)

(untitled) - Zhang, B.; Zhu, S.-F.; Zhou, Q.-L. (Tetrahedron, 2013)

(untitled) - Kumar, Y.; Jaiswal, Y.; Kumar, A. (J. Org. Chem., 2016)

(untitled) - Yi, C. S.; Kwon, K.-H.; Lee, D. W. (Org. Lett., 2009)

(untitled) - Catino, A. J.; Nichols, J. M.; Choi, H.; Gottipamula, S.; Doyle, M. P. (Org. Lett., 2005)

(untitled) - Bonvin, Y.; Callens, E.; Larrosa, I.; Henderson, D. A.; Oldham, J.; Burton, A. J.; Barrett, A. G. M. (Org. Lett., 2005)

(untitled) - Lu, B.; Zhu, F.; Sun, H.-M.; Shen, Q. (Org. Lett., 2017)

(untitled) - Tomás, R. A. F.; Bordado, J. C. M.; Gomes, J. F. P. (Chem. Rev., 2013)

(untitled) - Baran, P. S.; Zhong, Y.-L. (J. Am. Chem. Soc., 2001)

(untitled) - Ojha, L. R.; Kudugunti, S.; Maddukuri, P. P.; Kommareddy, A.; Gunna, M. R.; Dokuparthi, P.; Gottam, H. B.; Botha, K. K.; Parapati, D. R.; Vinod, T. K. (Synlett, 2009)

(untitled) - Qian, P.-C.; Liu, Y.; Song, R.-J.; Hu, M.; Yang, X.-H.; Xiang, J.-N.; Li, J.-H. (Eur. J. Org. Chem., 2015)

(untitled) - Baba, H.; Moriyama, K.; Togo, H. (Tetrahedron Lett., 2011)

(untitled) - Sakamoto, R.; Inada, T.; Selvakumar, S.; Moteki, S. A.; Maruoka, K. (Chem. Commun., 2016)

(untitled) - Dohi, T.; Ueda, S.; Iwasaki, K.; Tsunoda, Y.; Morimoto, K.; Kita, Y. (Beilstein J. Org. Chem., 2018)

(untitled) - Dohi, T.; Takenaga, N.; Goto, A.; Fujioka, H.; Kita, Y. (J. Org. Chem., 2008)

(untitled) - Shaikh, T. M.; Sudalai, A. (Tetrahedron Lett., 2005)

(untitled) - Wu, X.-F.; Gong, J.-L.; Qi, X. (Org. Biomol. Chem., 2014)

(untitled) - Xu, Y.; Yang, Z.; Hu, J.; Yan, J. (Synthesis, 2013)

(untitled) - Artaryan, A.; Mardyukov, A.; Kulbitski, K.; Avigdori, I.; Nisnevich, G. A.; Schreiner, P. R.; Gandelman, M. (J. Org. Chem., 2017)

(untitled) - Combe, S. H.; Hosseini, A.; Song, L.; Hausmann, H.; Schreiner, P. R. (Org. Lett., 2017)

(untitled) - Kumar, V.; Sharma, A.; Sharma, M.; Sharma, U. K.; Sinha, A. K. (Tetrahedron, 2007)

(untitled) - Xiang, M.; Xin, Z.-K.; Chen, B.; Tung, C.-H.; Wu, L.-Z. (Org. Lett., 2017)

(untitled) - Pandey, G.; Laha, R.; Singh, D. (J. Org. Chem., 2016)

(untitled) - Xia, J.-B.; Zhu, C.; Chen, C. (J. Am. Chem. Soc., 2013)

(untitled) - Jin, C.; Zhang, L.; Su, W. (Synlett, 2011)

(untitled) - Moriyama, K.; Takemura, M.; Togo, H. (Org. Lett., 2012)

(untitled) - Chen, K.; Zhang, P.; Wang, Y.; Li, H. (Green Chem., 2014)

(untitled) - Coseri, S. (Catal. Rev.: Sci. Eng., 2009)

(untitled) - Melone, L.; Punta, C. (Beilstein J. Org. Chem., 2013)

(untitled) - Recupero, F.; Punta, C. (Chem. Rev., 2007)

(untitled) - Ishii, Y.; Sakaguchi, S.; Iwahama, T. (Adv. Synth. Catal., 2001)

Encyclopedia of Reagents for Organic Synthesis - Gambarotti, C.; Punta, C.; Recupero, F.; Zlotorzynska, M.; Sammis, G. (N-Hydroxyphthalimide, 2013)

(untitled) - Eikawa, M.; Sakaguchi, S.; Ishii, Y. (J. Org. Chem., 1999)

(untitled) - Minisci, F.; Recupero, F.; Gambarotti, C.; Punta, C.; Paganelli, R. (Tetrahedron Lett., 2003)

(untitled) - Gunchenko, P. A.; Li, J.; Liu, B.; Chen, H.; Pashenko, A. E.; Bakhonsky, V. V.; Zhuk, T. S.; Fokin, A. A. (Mol. Catal., 2018)

(untitled) - Fortman, G. C.; Boaz, N. C.; Munz, D.; Konnick, M. M.; Periana, R. A.; Groves, J. T.; Gunnoe, T. B. (J. Am. Chem. Soc., 2014)

(untitled) - Kalman, S. E.; Munz, D.; Fortman, G. C.; Boaz, N. C.; Groves, J. T.; Gunnoe, T. B. (Dalton Trans., 2015)

(untitled) - Schwartz, N. A.; Boaz, N. C.; Kalman, S. E.; Zhuang, T.; Goldberg, J. M.; Fu, R.; Nielsen, R. J.; Goddard, W. A., III; Groves, J. T.; Gunnoe, T. B. (ACS Catal., 2018)

(untitled) - Gorgy, K.; Lepretre, J.-C.; Saint-Aman, E.; Einhorn, C.; Einhorn, J.; Marcadal, C.; Pierre, J.-L. (Electrochim. Acta, 1998)

(untitled) - Amaoka, Y.; Nagatomo, M.; Inoue, M. (Org. Lett., 2013)

(untitled) - Kiyokawa, K.; Ito, R.; Takemoto, K.; Minakata, S. (Chem. Commun., 2018)

(untitled) - Kiyokawa, K.; Takemoto, K.; Minakata, S. (Chem. Commun., 2016)

Comprehensive Handbook of Chemical Bond Energies - Luo, Y. R. (CRC Press)

(untitled) - Minisci, F.; Recupero, F.; Cecchetto, A.; Gambarotti, C.; Punta, C.; Paganelli, R.; Pedulli, G. F.; Fontana, F. (Org. Process Res. Dev., 2004)

(untitled) - Laudadio, G.; Govaerts, S.; Wang, Y.; Ravelli, D.; Koolman, H. F.; Fagnoni, M.; Djuric, S. W.; Noël, T. (Angew. Chem., Int. Ed., 2018)

(untitled) - Ishii, Y.; Iwahama, T.; Sakaguchi, S.; Nakayama, K.; Nishiyama, Y. (J. Org. Chem., 1996)

(untitled) - Hock, H.; Lang, S. (Ber. Dtsch. Chem. Ges. B, 1944)

(untitled) - Seubold, F. H., Jr; Vaughan, W. E. (J. Am. Chem. Soc., 1953)

(untitled) - Amorati, R.; Lucarini, M.; Mugnaini, V.; Pedulli, G. F.; Minisci, F.; Recupero, F.; Fontana, F.; Astolfi, P.; Greci, L. (J. Org. Chem., 2003)

(untitled) - Koshino, N.; Saha, B.; Espenson, J. H. (J. Org. Chem., 2003)

(untitled) - Opeida, I. A.; Litvinov, Y. E.; Kushch, O. V.; Kompanets, M. A.; Shendrik, A. N.; Matvienko, A. G.; Novokhatko, A. A. (Russ. J. Phys. Chem. A, 2016)

(untitled) - Horn, E. J.; Rosen, B. R.; Chen, Y.; Tang, J.; Chen, K.; Eastgate, M. D.; Baran, P. S. (Nature, 2016)

(untitled) - Amaoka, Y.; Kamijo, S.; Hoshikawa, T.; Inoue, M. (J. Org. Chem., 2012)

(untitled) - Marchaj, A.; Kelley, D. G.; Bakac, A.; Espenson, J. H. (J. Phys. Chem., 1991)

(untitled) - Mezyk, S. P.; Madden, K. P. (J. Phys. Chem., 1996)

(untitled) - Hook, S. C. W.; Saville, B. (J. Chem. Soc., Perkin Trans. 2, 1975)

(untitled) - Rueda-Becerril, M.; Chatalova Sazepin, C.; Leung, J. C. T.; Okbinoglu, T.; Kennepohl, P.; Paquin, J.-F.; Sammis, G. M. (J. Am. Chem. Soc., 2012)

(untitled) - Rafiee, M.; Wang, F.; Hruszkewycz, D. P.; Stahl, S. S. (J. Am. Chem. Soc., 2018)

(untitled) - Zhang, H.; Muñiz, K. (ACS Catal., 2017)